Effect of Rural-Urban Migration on Education and Economics Development - Iderawumi, Abdulraheem Mukhtar; Abiodun, Iderawumi Mubarakat (American Journal of Trade and Policy, 2019)
Over the years, demands for education have become progressively more insistent, more persuasive and complex. The kind of education given impinges on society in a variety of ways to meet an ever-widening range of needs. This research is to examine the effect of rural-urban migration on education and economic development with reference to Ibarapa East Local Government Area of Oyo State. The man and specific motives are to find out the causes of rural-urban migration how it affects the students’ performance and aimed at examining its effect on productivity level of Ibarapa East Local Government Area. The instrument used for collecting the data is the questionnaire. Hypotheses were formulated, whereas simple percentage methods were used to analyze the data. The finding shows that there are the different impacts of rural-urban migration on education and development of Ibarapa East Local Government causes short fall of the labour force, short of qualified and low productivity especially in the agricultural sector. Rural-urban migration contributes to the high rate of unemployment. It increases the number of juvenile delinquencies crimes and other social vices in the society, and it has effect on the educational development of the study area. Based on all the findings, recommendation was made that the government should provide social and infrastructural facilities such as good road network, regular supply of electricity and so on for rural dwellers. And also with the various youth programs, it could be possible to reduce rural-urban migration, most especially when the young ones are exposed to sustainable livelihood activities that they could embark upon.